AB0454 FREQUENCY AND DURATION OF EARLY NON-SERIOUS ADVERSE EVENTS IN RHEUMATOID ARTHRITIS PATIENTS TREATED WITH TOFACITINIB 5 MG TWICE DAILY AS MONOTHERAPY AND COMBINATION THERAPY. (June 2019) - Dikranian, Ara; Wollenhaupt, Jürgen; Azevedo, Valderilio F.; Bessette, Louis; Gold, David; Rivas, Jose Luis; Shi, Harry; Wang, Lisy; Woolcott, John; Shapiro, Andrea; Nash, Peter
Abstract : Background: Tolerability remains ill-defined in clinical trials and commonly refers to non-serious adverse events (AEs) impacting patient (pt) satisfaction and treatment adherence. Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). Objectives: This update to a previously published post hoc analysis 1 describes the frequency and duration of the most common tolerability-related non-serious AEs in pts with RA receiving tofacitinib 5 mg BID as monotherapy or with conventional synthetic (cs)DMARDs in Phase (P)3 and P3b/4 studies. Methods: Data were pooled from: ORAL Step (NCT00960440 ); ORAL Solo (NCT00814307 ); ORAL Scan (NCT00847613 ); ORAL Sync (NCT00856544 ); ORAL Standard (NCT00853385 ); and ORAL Strategy (NCT02187055 ). This post hoc analysis included data from pts receiving tofacitinib 5 mg BID monotherapy (ORAL Solo, ORAL Strategy), placebo (PBO; ORAL Solo), or tofacitinib 5 mg BID or PBO with csDMARDs (all studies except ORAL Solo). Non-serious AEs (affecting pts' day-to-day experience and ability to tolerate therapy) with incidence rates (IRs, pts with events/100 pt-years) ≥5 were evaluated up to Month (M)3. Infections, laboratory test abnormalities, general disorders or events not directly reported by pts, and musculoskeletal disorders likely due to underlying RA, were excluded. Results: Of the 2657 pts included in the analysis, 1976 received tofacitinib 5 mg BID (monotherapy: N=627; combination: N=1349) and 681 received PBO (monotherapy: N=122; combination: N=559). The most frequent non-serious AEs up to M3 are shown in the Table. IRs ≥10 were seen for headache and diarrhoea (tofacitinib 5 mg BID monotherapy, combination therapy and PBO monotherapy), and nausea (PBO monotherapy and PBO combination therapy). Non-serious AE duration was ≤4 weeks for most pts with headaches, diarrhoea or gastric discomfort (any gastrointestinal pain, dyspepsia, epigastric discomfort or abdominal discomfort/pain). With tofacitinib 5 mg BID and PBO, respectively, duration of AEs was ≤2 weeks for 43.2% and 64.7% of pts with headaches; 66.1% and 81.3% with diarrhoea; and 36.2% and 58.6% with gastric discomfort. Most non-serious AEs were mild/moderate. Conclusion: Overall, non-infectious non-serious AEs were mild/moderate and the majority were self-limiting. Non-serious AE frequency was similar for tofacitinib monotherapy and combination therapy, and for tofacitinib and PBO. References: [1] Dikranian A, et al. Arthritis Rheumatol 2013; 65: S192. Acknowledgement: Study sponsored by Pfizer Inc. Medical writing support was provided by Anthony G McCluskey of CMC Connect and funded by Pfizer Inc. Disclosure of Interests: Ara Dikranian Consultant for: AbbVie, Pfizer Inc, Speakers bureau: AbbVie, Pfizer Inc, Jürgen Wollenhaupt Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, Valderilio F Azevedo Grant/research support from: AbbVie, GSK, Janssen, Merck Serono, Novartis, Pfizer Inc, UCB, Consultant for: AbbVie, GSK, Janssen, Merck Serono, Novartis, Pfizer Inc, UCB, Louis Bessette Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant for: AbbVie, Celgene, Eli Lilly, Novartis, Pfizer Inc, David Gold Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Jose Luis Rivas Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Harry Shi Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Lisy Wang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, John Woolcott Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Andrea Shapiro Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Peter Nash Grant/research support from: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Consultant for: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, Janssen, Novartis, Pfizer Inc, Roche, Sanofi, UCB